Stably maintained microdomain of localized unrestrained supercoiling at a Drosophila heat shock gene locus. - Jupe, E.R.; Sinden, R.R.; Cartwright, I.L. (The EMBO Journal, 1993)
A psoralen crosslinking assay was utilized to detect localized, unrestrained DNA supercoiling (torsional tension) in vivo in Drosophila chromosomal regions subject to differential transcriptional activity. By comparing rates of crosslinking in intact cells with those in cells where potential tension in chromosomal domains was relaxed by DNA strand nicking, the contribution to psoralen accessibility caused by altered DNA-protein interactions (e.g. nucleosomal perturbations) was distinguished from that due to the presence of unrestrained supercoiling in a region of interest. The heat shock protein 70 (hsp70) genes were wound with a significant level of superhelical tension that remained virtually unaltered whether or not the genes were transcriptionally activated by thermal elevation. Constitutively expressed 18S ribosomal RNA genes also exhibited unrestrained superhelical tension at a level comparable with that across hsp70. In contrast, flanking regions downstream of each of the divergent hsp70 genes at locus 87A7 exhibited substantially less tension. Thus the results point to the existence of stable, torsionally stressed topological domains within eukaryotic chromosomal DNA, suggesting that the relaxing action of topoisomerases is not ubiquitous throughout the nucleus but, in fact, is likely to be tightly regulated.